(untitled) (International Journal of Engineering and Computer Science, 2019)
Consulting services are among the most lucrative and fastest growing sectors of the global economy. COVID-19 acted as a catalyst for their transition to online platforms. Most traditional advisory services are now performed on digital bases, sometimes through tailored digital marketing, and their clients’ portfolios are reduced compared to the pre-COVID-19 period, as a rule. However, these two factors are not sufficient to determine new scalable business models in consulting. Only some clients are receptive to such models, and only some advisory services can be successfully digitized. Global historical data developments in consulting and their key 20 subsectors are analyzed in time dimension to reveal the law of motion of their digitalization process. The results indicate that the pandemic-induced changes in the consulting market are not just temporary. Alarming warnings about the traditional consultants’ business models and revenues’ recession can have a sound microeconomic background when they move from face-to-face interactions to online platforms. A primary conclusion is that horizontal platforms providing consultations in digitalized services cannot yet fully replace traditional consulting firms. Traditional face-to-face consulting service delivery is pivoting increasingly quickly to scalable digital platforms. The COVID-19 pandemic accelerated this structural shift. Many traditional services are already offerable only via cloud-based technologies, from digital marketing to fully automated customs clearance services with the help of AI tools and other digital technologies. However, the observed trends will not be sufficient for a fully scalable sustainable new digital platform business model in the consulting industry. Among the key questions, the rationales of such a transition as well as customers’ willingness to pay for consulting and specific services delivered in that way need to be analyzed. In what follows, this study analyzes this service digitalization process quantitatively for the whole industry worldwide as well as for its subsectors and specific digitalized activities and information sectors after providing a theoretical model to rationalize these empirics. We conclude this article with policy implications for the consulting industry.